The Effectiveness of Google Classroom Usage In the PPISMP Students’ Interaction : A Survey - Zaharah Mohamad Mohamad; Nor Azizah Atan; Badariah Mohamed; Tetep Tetep (Institut Pendidikan Indonesia, 2022)
This study aims to observe the effectiveness of Google Classroom Usage for the Art History of Malaysia and Visual Art Appreciation course by the PPISMP Students. Students have used the Google Classroom as an e-learning teaching and learning platform during the Movement Control Order (MCO)due to Covid-19 pandemic. The Research Design is quantitative and qualitative using questionnaire and survey method. The respondents are 29 PPISMP students who were taking the Art History of Malaysia and Visual Art Appreciation course. From the research objectives it is found that majority of the respondents really agreed that lecturers always gave latest information in their e-learning teaching and learning using Google Classroom platform. Majority of the respondents really agreed Google Classroom usage can increase students’ ability in applying knowledge and understanding acquired in the Art History of Malaysia and Visual Art Appreciation course. Research finding shows that activity type which often used by students are taking note and lecture materials and submitting assignments and tasks to lecturers.